Relationship Between Trust and Perceived Quality of Healthcare Services - Krawczyńska, Aleksandra (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The issue of trust as an ethical foundation of social infrastructure has always aroused intense interest among social scientists. With the development of the concept of relationship marketing, trust and its impact on the efficiency of the organization has also become a subject of research. The results of these studies show indisputably that the acquisition and maintenance of trust is a key factor in building and developing long-term relationships and valuable service. It is essential that there may be a transfer of knowledge, and cooperation agreements between the two sides. Trust is also an essential part of intangible assets. It is not surprising that research on the issues of trust are carried out in different sectors in this important sector of healthcare services. However, due to the multitude of work and research as well as a variety of approaches to the issues of trust, its determinants and consequences, aim of this article is to analyse this issue on the basis of the perceived healthcare service quality.